The development and evaluation of a short-term international student research and educational program - Ubolrat Piamjariyakul; Saima Shafique; Dana L. Friend; Kimberly A. Adams; Wiyakarn Sanghuachang; Trisha M. Petitte; Stephanie Young (Elsevier, 2024)
Objectives: This study aimed to describe the "how-to" details and processes for developing and evaluating a short-term international student research and education program. Methods: This study included two parts: development and implementation, and evaluation of the program. A foreign doctoral nursing student requested to visit the West Virginia University School of Nursing for research training and academic teaching experience. The global nursing program coordinator and the lead mentor met and identified the program basis and team participants. Learning activities were related to this student's interest in older adults and in-home end-of-life care, included four contents: research; educational engagement; practice/clinical engagement; special activities & professional development training and courses. The program evaluation was conducted at the end of the six-month visit using a focus group and an anonymous short survey. Participants (n = 10) included the host university's faculty, graduate students, and one short-term international student. Results: Content analysis of the participant's short survey answers and the focus group discussion resulted in three themes: 1) lessons learned from participating in the program (enhanced diversity in education and research, gaining new global healthcare knowledge, and self-reflection on and promoting cultural awareness); 2) program barriers and challenges (the visa application process, the English language barrier, the lack of public transportation in the town, and scheduling conflicts); and 3) strategies to overcome these barriers and challenges (adding cultural diversity information into curriculum; attending English proficiency with others in the class; using different communication techniques; continuous collaboration with the University's Office of Global Affairs for the Visa application process; providing interactive experiences). All participants rated their engagement in the program as very satisfactory (Mean = 4.67, SD = 0.50), and highly impacted their nursing skills in research, teaching, and clinical practice (Mean = 4.67, SD = 0.50). Conclusions: All the participants have gained some experience in this program, which can be used for future teaching guidance. Further, international nursing students need assistance to adjust and thrive in the host university learning community. Faculty must be culturally sensitive, understand the visiting foreign nursing student' learning needs, and advocate for an environment suitable for enhancing the students' learning.